Pembelajaran Online pada Masa Pandemi Covid-19 Meningkatkan Kesulitan Belajar Matematika pada Siswa Sekolah Dasar - Annisah, Siti; Masfiah, Siti (Institut Agama Islam Negeri Palangka Raya, 2021)
Online learning during the Covid-19 pandemic made elementary students even more difficult to master math material. The purpose of this study was to describe how online learning can increase the difficulty of learning mathematics for elementary school students. This research was conducted in a descriptive qualitative manner involving 31 students, 9 parents, and class IV teachers of MIN 4 East Lampung. Interviews and documentation are used to obtain primary and secondary data. Data analysis was carried out in three stages, namely reduction, display, and data verification. The findings of this study are 1) there has been a decrease in mathematics learning outcomes in elementary school students as a result of online learning, 2) an increase in mathematics learning difficulties experienced by students in online learning, and 3) aspects that cause an increase in mathematics learning difficulties in online learning. Thus online learning at the beginning of the Covid-19 epidemic had a negative impact on increasing math learning difficulties for elementary school students.